Informelle Pflege bei Demenz nach Leistungsarten = Informal care for dementia according to type of service - Brettschneider, Christian; Werle, Jochen; Weyerer, Siegfried (Der Nervenarzt, 2018)
Background Dementia is a major challenge for society and its impact will grow in the future. Informal care is an essential part of dementia care. Previous studies considered informal care as a whole and not by its components.ObjectiveWe aimed to assess the degree of association between specific informal care services and dementia.Material and methodsThis analysis is based on data from the seventh wave of the AgeCoDe/AgeQualiDe study. Dementia was diagnosed based on the DSM-IV criteria. Severity of dementia was assessed and categorized by means of the Clinical Dementia Rating and eight individual informal care services were considered. Logistic regression models were used to assess associations.ResultsOf the 864 participants 18% suffered from dementia (very mild: 4%; mild: 6%; moderate: 5%; severe: 3%). All informal care services were significantly associated with dementia, with an emphasis on “supervision”, “regulation of financial matters” and “assistance in the intake of medication”. Considering different degrees of dementia severity, similar results arose from the analyses. All three aforementioned services showed a pronounced association with all degrees of dementia severity, except for supervision and very mild dementia.ConclusionThe provision of all types of informal care services is associated with dementia. The association is pronounced for services that can be more easily integrated into the daily routines of the informal caregiver. Policy makers who plan to integrate informal care into the general care arrangements for dementia should consider this.